Intracranial Pressure Modulates Distortion Product Otoacoustic Emissions: A Proof-of-Principle Study - Bershad, Eric M.; Urfy, Mian Z.; Pechacek, Alina; McGrath, Mary; Calvillo, Eusebia; Horton, Nicholas J.; Voss, Susan E. (Neurosurgery, 2014)
BACKGROUND:There is an important need to develop a noninvasive method for assessing intracranial pressure (ICP). We report a novel approach for monitoring ICP using cochlear-derived distortion product otoacoustic emissions (DPOAEs), which are affected by ICP. OBJECTIVE:We hypothesized that changes in ICP may be reflected by altered DPOAE responses via an associated change in perilymphatic pressure. METHODS:We measured the ICP and DPOAEs (magnitude and phase angle) during opening and closing in 20 patients undergoing lumbar puncture. RESULTS:We collected data on 18 patients and grouped them based on small (<4 mm Hg), medium (5-11 mm Hg), or large (≥15 mm Hg) ICP changes. A permutation test was applied in each group to determine whether changes in DPOAEs differed from zero when ICP changed. We report significant changes in the DPOAE magnitudes and angles, respectively, for the group with the largest ICP changes and no changes for the group with the smallest changes; the group with medium changes had variable DPOAE changes. CONCLUSION:We report, for the first time, systematic changes in DPOAE magnitudes and phase in response to acute ICP changes. Future studies are warranted to further develop this new approach. ABBREVIATIONS:DPOAE, distortion product otoacoustic emissionICP, intracranial pressureIIH, idiopathic intracranial hypertensionLP, lumbar punctureTBI, traumatic brain injury